Acquisition of Demonstratives in English and Spanish - González-Peña, Patricia; Doherty, Martin J.; Guijarro-Fuentes, Pedro (Frontiers in Psychology, 2020)
The present work re-evaluates the long-standing claim that demonstratives are among infants’ earliest and most common words. Although demonstratives are deictic words important for joint attention, deictic gestures and non-word vocalizations could serve this function in early language development; the role of demonstratives may have been overestimated. Using extensive data from the CHILDES corpora (Study 1, N = 66, 265 transcripts) and McArthur-Bates CDI database (Study 2, N = 950), the language production of 18- to 24-month-old Spanish- and English-speaking children was analyzed to determine the age and order of acquisition, and frequency of demonstratives. Results indicate that demonstratives do not typically appear before the 50th word and only become frequent from the two-word utterance stage. Corpus data show few differences between Spanish and English, whereas parental report data suggest much later acquisition for demonstratives in English. These findings expand our knowledge of the foundations of deictic communication, and of the methodological challenges of assessing early production of function words.